2016
DOI: 10.1111/jcms.12485
|View full text |Cite
|
Sign up to set email alerts
|

The Desire for Sovereignty – An Explanation of EU Attitudes in the Arab World

Abstract: A growing body of survey research shows that the European Union (EU) has a relatively benign image around the world, except among Arab populations. What informs Arab citizens' sceptical attitudes toward the European Union (EU)? Combining literature on Arab public opinion and perceptions of the EU, we argue that Arab citizens' feelings about the EU are influenced most prominently by their desire for sovereignty. Moreover, traditional utilitarian and cue-taking mechanisms should also impact Arab EU attitudes. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In a similar vein, Steiner (2018) has argued most recently that the varying degrees of skepticism toward Transatlantic Trade and Investment Partnership (TTIP) across European countries can be predicted by the aggregate and individual levels of anti-Americanism, with people in countries with higher levels of anti-American feelings being more critical of TTIP. Similarly, Isani and Schlipphak (2017b) have shown that Arab citizens' feelings toward the US are strongly shaping their attitudes toward other Western organizations, such as the EU.…”
Section: Elite Vs Societal Cueinga General Theoretical Argumentmentioning
confidence: 99%
“…In a similar vein, Steiner (2018) has argued most recently that the varying degrees of skepticism toward Transatlantic Trade and Investment Partnership (TTIP) across European countries can be predicted by the aggregate and individual levels of anti-Americanism, with people in countries with higher levels of anti-American feelings being more critical of TTIP. Similarly, Isani and Schlipphak (2017b) have shown that Arab citizens' feelings toward the US are strongly shaping their attitudes toward other Western organizations, such as the EU.…”
Section: Elite Vs Societal Cueinga General Theoretical Argumentmentioning
confidence: 99%
“…Most studies have focused on elites (e.g. Arynov, 2022;Bengtsson and Elgström, 2012;Chaban et al, 2013;Chaban and Kelly, 2017), while a few have explored external perceptions of the EU beyond elites and looked at the general public (Chaban et al, 2015(Chaban et al, , 2021Chaban and Holland, 2019;Isani and Schlipphak, 2017). Public opinions about the EU have become more important as the EU has developed the means and tools for public diplomacy (Speyer et al, 2021).…”
Section: The Normative Power Of Europe and External Perceptions Of Th...mentioning
confidence: 99%
“…Numerous studies have examined the EU's message and how it is perceived by the receiver (especially the elites) outside the EU (Chaban et al, 2013;Chaban and Kelly, 2017;Pardo, 2015;Speyer et al, 2021). One line of estimation of how the EU is perceived by the public is the research subfield of external perceptions of the EU (Ananieva, 2020;Chaban et al, 2015Chaban et al, , 2021Chaban and Holland, 2019;Isani and Schlipphak, 2017;Kelly and Mochan, 2021;Lucarelli, 2014). These studies have provided a valuable description of attitudes toward the EU around the globe (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The level of influence the EU seeks to exercise on the international level encounters a large amount of criticism: the EU is accused of westernising the world. 44 From a legal perspective, the future of EU sanctions stays highly unpredictable and above all contentious. The strong international presence of the EU particularly through its sanctioning schemes raises controversy as to its legality.…”
Section: Iv2 Other Related Eu Actions Under Cfsp: Analysis and Criticismmentioning
confidence: 99%